Photodegradation of Chloridazon Using Coreshell Magnetic Nanocompsites - Dina Mamdouh Fouad; Mona Bakr Mohamed (Journal of Nanotechnology)
A new synthesized magnetic nanoparticle of Fe3O4 and coreshell Fe3O4@Au is prepared chemically. A comparative study between the photocatalytic activity between Fe3O4 and core shell Au-Fe3O4 nanoparticles has been studied on the effect of UV and sun light on the photodegradation of chloridazon. The particle has been prepared using chemical methods and the particle size and shape have been examined via transmission electron microscopy (TEM). Analysis of the degradation of 20 ppm chloridazon under ultraviolet (UV) and visible light was analyzed with high-performance liquid chromatography (HPLC) and UV-Visible Spectra. Influence of different parameters on the activity photodegradation rate has been studied. The results indicate that the Fe3O4@Au nanoparticles are much more active catalyst in presence of sun light than pure Fe3O4 nanomaterials which have maximum absorption at 560 nm.